Social management of the trust in the preparation of the olympic sports reserve: concept and methodological foundations - M. Yu. Burtsov (Вестник университета, 2019)
The author’s approach to clarifying the concept and essence of the concept of «trust» in the sports field, as well as trust management, - has been presented. The characteristic of the modern sociological concept of management has been given, the sources in disclosure of this problem have been described. The level offormation, as well as the subject content of relations of trust between different subjects of sports activity in the Olympic reserve system in our country at the present time has been revealed. The method of social diagnostics of relations of trust in sports teams has been described, the characteristic of the relevance of collection methods has been given. The author’s proposals to improve the efficiency of the process of social management of relations of trust in the system ofpreparation of the Olympic reserve have been presented.